Epidermal growth factor loaded heparin-based hydrogel sheet for skin wound healing. (20th August 2016) - Goh, MeeiChyn; Hwang, Youngmin; Tae, Giyoong
Highlights: Heparin-based hydrogel sheet was prepared via photo polymerization. Appropriate as a wound dressing due to quick water uptake ability, and suitable water evaporation rate and mechanical strength. hEGF loaded heparin-based hydrogel resulted in the enhanced wound healing in an animal model. Abstract: A heparin-based hydrogel sheet composed of thiolated heparin and diacrylated poly (ethylene glycol) was prepared via photo polymerization and human epidermal growth factor (hEGF) were loaded into it for the purpose of wound healing. It showed a sustained release profile of hEGF in vitro . In order to evaluate its function on wound healing in vivo, full thickness wounds were created on the dorsal surface of mice. Application of hEGF loaded heparin-based hydrogel sheet accelerated the wound closure compared to the non-treated control group, hEGF solution, and hEGF loaded PEG hydrogel sheet. Histological and immunohistological examinations also demonstrated an advanced granulation tissue formation, capillary formation, and epithelialization in wounds treated by hEGF loaded heparin-based hydrogel compared to other groups, and no biocompatibility issue was observed. In conclusion, the delivery of hEGF using the heparin-based hydrogel could accelerate the skin wound healing process.